Case Report: Medical Management of Prolonged Gestation of a Mummified Fetus in a Bitch - Spruijt, Annemarie; van Stee, Lucinda; Wolthers, Karin; de Gier, Jeffrey (Frontiers in Veterinary Science, 2022)
A 3-year-old female rough coated collie was presented at day 69 (D69) after the first mating. She was mated on two consecutive days based on ovulation timing by the referring veterinarian. At day 30 post breeding, a single, live embryo was seen on ultrasound by this veterinarian. On D69, the bitch was presented to us because she lacked signs of impending parturition such as vulvar discharge or nest building behavior. On general examination, the bitch appeared clinically healthy and no prodromi were present. On abdominal palpation a small, firm structure and a slightly enlarged uterus were detected. There was no vulvar discharge. Using vaginoscopy we could not see any signs of cervical dilatation. Additionally, ultrasonography revealed the presence of a collapsed fetus in the uterus with a moderate amount of echogenic fluid surrounding it and the plasma progesterone concentration was 2.6 ng/ml. A parturition induction protocol was initiated: a progesterone receptor antagonist was administered, followed by PGF2α to induce cervical relaxation and uterine contractions. The fetus was expelled 3 days later, without noticeable damage to the reproductive tract of the dam. The bitch subsequently delivered two more litters without complications. To our knowledge this is the first clinical report that demonstrates a successful non-surgical treatment to expel a mummified fetus after prolonged gestation. The pharmacological treatment did not affect the future fertility of the breeding dog, which is an important outcome for breeders.